Studi Tanda Atas Makna Pelesarian Lingkungan Sebagai Isu Utama Konten Kreatif Media Sosial - Fitrya Basarah, Finy (Communication, 2019)
The balance of nature could not be separated from human interactions, both destructive acts and those that supported the conservation of nature and the environment. Nowadays, quite a lot of environmental issues through some campaign rises up via social media in the form of vlogs, or video blogging. By utilizing Charles Sanders Peirce’s Semiotics Analysis, this research is done to uncover the meanings behind these environmental vlog contents. There are three vlogs chosen in this research, all of them are from YouTube.com. The results show that Health is an Investment, Conjoining with nature can be done together, and the conservation of environment cannot be done alone, and must be done together.